2021
DOI: 10.1016/j.engfailanal.2021.105764
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear three-dimensional anisotropic material model for failure analysis of timber

Abstract: In this paper, a constitutive material model is proposed to model the nonlinear mechanical response of timber, as elastoplastic orthotropic material under three-dimensional (3D) stress state. An associated flow rule model based on Hoffmann yield criterion and plastic potential is adopted for describing the plasticity of timber under compression. Isotropic strain hardening during plastic deformation is incorporated into Hoffman yield criterion by assuming that equivalent yield stress is a function of the equiva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 48 publications
(88 reference statements)
0
13
0
Order By: Relevance
“…Examples of other investigations where FEM reportedly produced predictions that corresponded well with experimental outcomes include the evaluation of mechanical behaviors of timber beams and joints by Khorsandnia et al [54] and multi-layered wooden beams with welded-through wood dowel by O'Loinsigh et al [15], load-slip behavior of nailed wood joints under cyclic loading by Chui et al [67], failure analysis of timber in bending, tension, and compression states by Eslami et al [53], strength properties of laminated veneer lumber in flat and edge-wise bending by Gilbert et al [68], non-linear flexural behavior of cross-insulated timber panel with polyurethane foam core by Santos et al [69], flexural behaviors of glulam timber arches by Smidova et al [70] and hybrid timber beams by Tran et al [51], and strength analysis of pine and beech wood dowel and tenon corner joints by Kaygin et al [28] to name a few.…”
Section: Other Examples Of Fea Of Wood and Swcs Propertiesmentioning
confidence: 83%
See 1 more Smart Citation
“…Examples of other investigations where FEM reportedly produced predictions that corresponded well with experimental outcomes include the evaluation of mechanical behaviors of timber beams and joints by Khorsandnia et al [54] and multi-layered wooden beams with welded-through wood dowel by O'Loinsigh et al [15], load-slip behavior of nailed wood joints under cyclic loading by Chui et al [67], failure analysis of timber in bending, tension, and compression states by Eslami et al [53], strength properties of laminated veneer lumber in flat and edge-wise bending by Gilbert et al [68], non-linear flexural behavior of cross-insulated timber panel with polyurethane foam core by Santos et al [69], flexural behaviors of glulam timber arches by Smidova et al [70] and hybrid timber beams by Tran et al [51], and strength analysis of pine and beech wood dowel and tenon corner joints by Kaygin et al [28] to name a few.…”
Section: Other Examples Of Fea Of Wood and Swcs Propertiesmentioning
confidence: 83%
“…Perhaps, establishing a relationship between meshing and specimen configuration could provide better FEA implementation considering the uniqueness of wood and other lignocellulosic fibers. Eslami et al [53] reported that meshing significantly influenced the softening stage of a modeled timber behavior. Besides, numerical solutions from FE simulations are mesh-dependent [14] thus it is crucial to adopt finite elements that will perform well under convoluted stress states [41].…”
Section: Fea Of Design Configuration and Size Effects On Mechanical P...mentioning
confidence: 99%
“…Therefore, in or-der to apply the ABS material properties obtained from the tensile tests to the finite element analysis, the orthotropic material constants must be estimated. The orthotropic material model for determining the orthotropic material constants can be defined as follows [17]. The 3-D printer used to produce the tensile test specimens was a fused filament fabrication output type, and the diameters of the nozzle and filament were 0.4 mm and 1.75 mm.…”
Section: Finite-element-analysis-based Strength Performance Evaluationmentioning
confidence: 99%
“…Chen et al [11] and Yang et al [12] established an elastic-plastic constitutive model. Based on continuum damage mechanics, three-dimensional elastic damage constitutive models of wood were proposed by Sandhaas et al [13], Gharib et al [14], Eslami et al [15], and Arruda et al [16], and elastic-plastic damage constitutive models by Sirumbalzapata et al [17], Wang et al [18], Benvenuti et al [19], and Zhang et al [20].…”
Section: Introductionmentioning
confidence: 99%